The Cognitive Science of Imagination and Religion. (1st November 2019) - van Mulukom, Valerie
Abstract : Religion and imagination both deal with what is beyond the empirical here and now. In this article, I will argue that imagination as a capacity is highly important for the development, maintenance, and evolution of religion and the variety of components that together make a religion: (Religious) belief, religious cognition broadly, religious events such as miracles, religious agents such as deities, religious rituals and experiences, religious texts and narratives, and finally religious art and creativity. I will argue that the cognitive science of imagination can crucially shed light on various aspects of religion that previously may have seemed unrelated, and that in fact, perceiving, remembering, and imagining may not be as distinct processes from each other as we might have thought, and indicate what consequences these suggestions may have for beliefs as we understand them.